Multicultural Education Approach in Forming Students' Positive Attitudes for Diversity in Indonesia - Muhammad Hifdil Islam (LP3M Universitas Islam Zainul Hasan Genggong, 2023)
This study aimed to highlight multicultural education approach in enhancing students' attitudes towards diversity in Indonesia has been gaining increasing attention in recent years. The objective of this theme is to promote a more inclusive and equitable educational environment by fostering positive attitudes towards diversity and inclusion among students. This is particularly important in the context of Indonesia, where there is significant cultural and religious diversity, and where students may be exposed to implicit messages of superiority and exclusivism through traditional teaching methods and practices. Multicultural education is seen as an effective approach to promoting positive attitudes towards diversity and inclusion. It involves teaching students about different cultures and backgrounds, and provides opportunities for students to interact with individuals from diverse backgrounds. The methodology of this research used library research. The research finding and discussion showed that there are several approach in multicultural education such as contribution approach, additive approach, the transformative approach, social action approach. In conclusion, the theme of multicultural education approach in enhancing students' attitudes towards diversity in Indonesia is of significant importance in the context of cultural and religious diversity in the country. By promoting understanding and respect for different cultures and perspectives, multicultural education can help to create a more inclusive and equitable educational environment for students.